STRATEGIES FOR TRANSFORMATIVE LEADERSHIP IN EDUCATIONAL SETTINGS: REALIZING EFFECTIVE IMPLEMENTATION GOALS - Emilya Zeynalova Faig (International Journal of Innovative Technologies in Social Science, 2024)
This journal explores the use of transformational leadership in educational settings, and how to implement it so that we can get good results. The development of positive change, innovation, and cultivation of educational institutions, in short, requires transformative leadership. Not only does the journal stress transformative leadership for its potential to improve learner performance and teacher practice, but there is mention that it can create the climate for favorable school conditions. It also introduces a variety of ways that leaders in education can be successful practicing transformative leadership.